Bending waveguides made in x-cut lithium niobate crystals for technological applications. (9th November 2015) - Guarepi, V; Perrone, C; Aveni, M; Videla, F; Torchia, GA
Abstract: In this paper we analyse the performance of several designs of integrated optical deviators made in x-cut lithium niobate crystals by means of femtosecond laser writing using the double line approach. Straight and bent guiding structures have been designed and implemented using this technique. Well-confined propagation modes at communication wavelengths (1.55 μ m) were conducted in these structures with acceptable overall losses (less than 2 dB cm −1 ). Further, a discussion about the optical propagation losses for curved and straight deviators devices is included in this work. At a low aperture angle (less than 0.2°), as expected, low losses were determined for both structures; however, a weak output light was observed for large angles (greater than 0.2°) in the straight optical circuits. In contrast, a smooth variation of the output was measured for the bent structures. The results presented in this paper support the possibility of the technological implementation of integrated optical circuits for optical communications fabricated with ultrashort laser writing in lithium niobate crystals. In addition, some hypotheses of loss mechanisms that are normally not considered are discussed in order to explain the differences between the measured values and predictions obtained by calculating with the usual models.